(untitled) (European Journal of Economics, Finance and Business Development, 2024)
In this article, in order to evaluate the factors of competitiveness of light industries, a questionnaire was conducted among the enterprises that are members of the "Uztoqimachiliksanoat" association and the "Uzbekcharmpoyabzali" association of textile, sewing-knitting and leather industry enterprises of Uzbekistan operating in the Zarafshan region. The questionnaire consisted of 37 questions representing factors grouped into 5 groups and 3 free questions.